"It was not that long!": The effects of the in-store TV screen content and consumers emotions on consumer waiting perception. (January 2015) - Borges, Adilson; Herter, Márcia Maurer; Chebat, Jean-Charles
Abstract: This paper explores the effects of retail environment distracters (TV screens) in reducing consumers׳ perceived waiting time and improving waiting satisfaction. Across two experiments, results show that retail environment distracters reduce perceived waiting time and increase consumers׳ waiting satisfaction, even when objective time is constant. More interestingly, findings indicate that retail environment distracters are more effective in increasing waiting perception when the content displayed is congruent with the retail context. In this case, findings suggest that emotions mediate the impact of congruent retail environment distracters on perceived waiting time and consumers׳ waiting satisfaction. Finally, this paper presents theoretical and managerial implications on how consumers react to retail environment distracters, emotions, perceived waiting time, and waiting satisfaction. Highlights: We explore the effects of retail environment distracters on consumer waiting perception. We examine different types of content displayed by the TV screens. The presence of TV screens reduces consumers׳ perceived waiting time and increases waiting satisfaction than the absence of TV screens, even when the objective waiting time is constant. The congruent content (vs. incongruent vs. absent) shows to be more efficient to reduce consumers׳ perceived waiting time and increase waiting satisfaction. Emotions mediate the effects between retail environment distracter and consumer waiting perception.